Myeloid-derived suppressor cells impair B cell responses in lung cancer through IL-7 and STAT5 - Wang, Yong (J Immunol, 2018)
Myeloid-derived suppressor cells (MDSCs) are known suppressors of anti-tumor immunity, affecting amino acid metabolism and T cell function in the tumor microenvironment (TME). However, it is unknown if MDSCs regulate B cell responses during tumor progression. Using a syngeneic mouse model of lung cancer, we show reduction in percentages and absolute numbers of B cell subsets including Pro-, Pre- and mature B cells in the bone marrow (BM) of tumor-bearing mice. The kinetics of this impaired B cell response correlated with the progressive infiltration of MDSCs. We identified that IL-7 and downstream STAT5 signaling that play a critical role in B cell development and differentiation were also impaired during tumor progression. Global impairment of B cell function was indicated by reduced serum IgG levels. Importantly, we show that anti-Gr-1 antibody-mediated depletion of MDSCs not only rescued serum IgG and IL-7 levels, but also reduced TGF-β1, a known regulator of stromal IL-7, suggesting MDSC-mediated regulation of B cell responses. Further, blockade of IL-7 resulted in reduced phosphorylation of downstream STAT5 and B cell differentiation in tumor-bearing mice and administration of TGF-β blocking antibody rescued these IL-7 dependent B cell responses. Adoptive transfer of BM-derived MDSCs from tumor-bearing mice into congenic recipients resulted in significant reductions of B cell subsets in the BM and in circulation. MDSCs also suppressed B cell proliferation in vitro in an arginase-dependent manner that required cell-to-cell contact. Our results indicate that tumor-infiltrating MDSCs may suppress humoral immune responses and promote tumor escape from immune surveillance.